Inserção externa e competitividade da Região Nordeste no período pós-abertura comercial: uma análise a partir do Método Shift-and-Share e de indicadores de competitividade revelada - Viana, Francisca Diana Ferreira (2006)
The objective main this study it were to analyze, through of indicators competitiveness of trade exterior, the exportations evolution of Northeast region and of the nine state (Alagoas, Bahia, Ceará, Maranhão, Paraíba, Pernambuco, Piauí, Rio Grande do Norte e Sergipe) in the period of 1995-2004. The specifics objectives it were: contexting the insert s Northeast region in the national economy; locating, through of the computing of indicators competitiveness, the sectors more dynamics, those that presented bigger productive, competitiveness and specialization to each state and region in the period in analyze; for last, it seeked to analyze the evolution of the exportations region through of the sift-share method. It conclusion were that composition exportations is of commodities and/or goods with small value in the international market. The region it owns a list of exportation focused in few goods, although the regions that buy the goods Northeast s regions are dynamics. The Northeast is very vulnerable the external demand.